2002
DOI: 10.1136/adc.86.5.376
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymes in blood of patients with Friedreich's ataxia

Abstract: Background and Aims: Increased generation of reactive oxygen species and mitochondrial dysfunction may underlie the pathophysiology of Friedreich's ataxia, the most common inherited ataxia, due to GAA expansion in a gene coding for a mitochondrial protein (frataxin), implicated in the regulation of iron metabolism. Because iron overload would cause oxidative stress in Friedreich's ataxia, we investigated the enzyme antioxidant system in the blood of 14 patients by determining superoxide dismutase, glutathione … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 37 publications
(30 reference statements)
1
20
0
1
Order By: Relevance
“…Reduced activities of mitochondrial holoproteins containing ironsulphur groups as well as an impairment of tissue energy metabolism have been demonstrated by biochemical and 31 P-MRS studies in cardiac and skeletal muscle from FRDA patients [9,[30][31][32][33]. Furthermore, the key role of oxidative stress in the pathophysiology of the disease has been supported by the finding of increased blood and urinary levels of oxidative stress markers in FRDA patients [13,16] as well as by in vivo evidence of impairment of antioxidant enzymes and of glutathione homeostasis [15,17].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Reduced activities of mitochondrial holoproteins containing ironsulphur groups as well as an impairment of tissue energy metabolism have been demonstrated by biochemical and 31 P-MRS studies in cardiac and skeletal muscle from FRDA patients [9,[30][31][32][33]. Furthermore, the key role of oxidative stress in the pathophysiology of the disease has been supported by the finding of increased blood and urinary levels of oxidative stress markers in FRDA patients [13,16] as well as by in vivo evidence of impairment of antioxidant enzymes and of glutathione homeostasis [15,17].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, other studies have found increased plasma and urinary levels of oxidative stress markers in FRDA patients [13][14][15][16][17] and have demonstrated that some antioxidants, such as idebenone and vitamin E, might have a protective role [18,19].…”
Section: Introductionmentioning
confidence: 97%
“…In fact, a reduction of free glutathione levels in the blood of patients with Friedreich ataxia, a total glutathione concentration comparable to the controls and a significant increase of glutathione bound to haemoglobin in erythrocytes have been demonstrated in FRDA patients [128], also associated with a significant elevation in the superoxide dismutase/ glutathione peroxidase activity ratio and with an 83% rise of glutathione transferase activity in the blood [129].…”
Section: Glutathione and Other Sh-containing Antioxidantsmentioning
confidence: 95%
“…In turn, O 2 -is generated by the direct addition to oxygen of electrons prematurely leaking from the respiratory chain, a leakage that increases when the respiratory chain is defective. H 2 O 2 is eliminated by mitochondrial glutathione peroxidase, at the expense of the small-molecule anti-oxidant glutathione, which appears to be decreased in FRDA, possibly because of excess consumption [10]. Another iron-independent mechanism of oxidative stress has been identified recently in frataxin-deficient yeast, which was observed to show signs of oxidative stress even in iron-depleted media, provided that they are cultured aerobically [11].…”
Section: ■ Oxidative Stressmentioning
confidence: 96%
“…In patients with FRDA, oxidative stress is revealed by increased plasma levels of malondialdehyde (a lipid peroxidation product) [16], increased urinary 8-hydroxy-2ʹ-deoxyguanosine (a marker of oxidative DNA damage) [17], decreased plasma free glutathione, and increased plasma glutathione-S-transferase activity [10]. It is intriguing that no evidence of oxidative stress was obtained in studies of conditional knockout mouse models [18], although results might have been confounded by various factors, including the admixture of cells having normal frataxin with progressively disappearing cells having no frataxin, and the almost complete shutdown of the respiratory chain in frataxindeficient cells (see the review in this supplement by Puccio).…”
Section: ■ Oxidative Stressmentioning
confidence: 99%